2023
DOI: 10.3389/fimmu.2022.1064007
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine/chemokine levels in the CSF and serum of anti-NMDAR encephalitis: A systematic review and meta-analysis

Abstract: ObjectivesTo summarize the cytokine/chemokine levels of anti-N-methyl-Daspartate receptor encephalitis (NMDAR-E) and explore the potential role of these molecules and immune cells in the pathogenic mechanism.MethodsThe PubMed, Cochrane Library, Embase, and Web of Science databases were searched for various articles that assessed the concentrations of cytokines/chemokines in the unstimulated cerebrospinal fluid (CSF) or serum of patients with NMDAR-E in this systematic review and meta-analysis. The standardized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 77 publications
0
7
0
Order By: Relevance
“…Interestingly, CXCL13 was identified as a biomarker with the highest predictive utility for the general recognition of neuroinflammation in the particular cohort [54]. Recently, a systematic review and meta-analysis by Ma et al (2023) [55] showed increased CSF concentrations of CXCL10 in patients with anti-Nmethyl-D-aspartate receptor encephalitis (NMDAR-E) compared with patients presenting with non-inflammatory neurological disorders, suggesting its possible diagnostic value in this model as well.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, CXCL13 was identified as a biomarker with the highest predictive utility for the general recognition of neuroinflammation in the particular cohort [54]. Recently, a systematic review and meta-analysis by Ma et al (2023) [55] showed increased CSF concentrations of CXCL10 in patients with anti-Nmethyl-D-aspartate receptor encephalitis (NMDAR-E) compared with patients presenting with non-inflammatory neurological disorders, suggesting its possible diagnostic value in this model as well.…”
Section: Discussionmentioning
confidence: 99%
“…Ventrally-induced mice also demonstrated decreased hippocampal NMDARs and intracerebral T cells and plasma cells 4 weeks after immunization. A recent metanalysis of cytokines from the blood and spinal fluid of NMDARE patients ( 5 ) demonstrated a predominance of T-cell-associated cytokines, along with some B-cell-related and broad-spectrum cytokines in the CSF of NMDARE patients, as compared to controls. There were elevations of IFN-γ, IL-1β, TNF-α, IL-6, IL-10, and IL-12 noted in NMDARE patients’ spinal fluid, cytokines which were included in the commercial pro-inflammatory kit we used.…”
Section: Discussionmentioning
confidence: 99%
“…However, the diagnosis and treatment of AE are currently hampered by an incomplete understanding of its pathogenesis. This is partly due to limited autopsy data ( 4 ) and relatively few immune-based studies in patients, such as cytokine profiling ( 5 ). As AE remains a comparatively rare disorder, translational animal models are needed to better elucidate its pathophysiology, which can lead to novel diagnostics and therapeutics.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, anti IL-6 agents can be used in conjunction with mycophenolate mofetil and azathioprine in a relatively safe way, as seen in NMOSD trial (SakuraSky). Given that IL-6 has been shown to be elevated in the CSF of many subtypes of AE ( 73 ), it has been therapeutically trialed in several types of autoimmune encephalitis. In a large institutional cohort of patients with refractory to rituximab AE, the tocilizumab group showed more frequent favorable mRS scores at 2 months from treatment initiation and at the last follow-up compared with the other groups.…”
Section: Il-6 Modulation In Autoimmune Encephalitismentioning
confidence: 99%